برصغیر میں مسلم عائلی قوانین کا ارتقاء: نفاذ اور اثرات کا جائزہ - شگفتہ عمر (FIKR-O NAZAR فکر ونظر, 2013)
The paper explores the corollaries of British intrusion on the Muslim Family Laws of the subcontinent. It tries to bring in the light the reasons that made the Imperial rule to do so. Moreover it examines the reaction of Muslim intellectuals and public at large against this onslaught and the effects that have been left in the legislation of the latter period.